Cold Creek Manor - Stewart, Annie; Figgis, Mike.; Jefferies, Richard, 1945-; Quaid, Dennis; Stone, Sharon, 1958-; Dorff, Stephen, 1973-; Lewis, Juliette; Stewart, Kristen, 1990-; Wilson, Ryan, 1990-; Eskelson, Dana.; Plummer, Christopher; Quinn, Declan, 1957-; et al. ([United States] : Touchstone Home Entertainment ; Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 2004)
The Tilson's are a wealthy couple who have grown tired of the high stress of life in New York City and are looking to move. Upstate, they find a mansion in the village of Cold Creek which has fallen into disrepair after it was repossessed. Convinced the house has great possibilities, the Tilsons buy it, and with a little hard work they are soon living in their dream home. Before long the family begins to learn the disturbing truth about the history of the mansion.
Widescreen.
Originally released as a motion picture in 2003.
Special features: bonus alternate ending; deleted scenes; "Rules of the genre" - director Mike Figgis gives insight into creating a psychological thriller; "Cooper's documentary" - a unique look at the creation of the documentary of the history of Cold Creek Monor and the Massie family; audio commentary with director.
Director of photography, Declan Quinn ; editor, Dylan Tichenor ; original music score, Mike Figgis ; costume designer, Marie-Sylvie Deveau ; production designer, Leslie Dilley.
Dennis Quaid, Sharon Stone, Stephen Dorff, Juliette Lewis, Kristen Stewart, Ryan Wilson, Dana Eskelson, Christopher Plummer.
MPAA rating: R; for violence, language and some sexuality.
Keywords: Mansions -- New York (State) -- Drama; Families -- Drama; Country life -- Drama; Ex-convicts -- New York (State) -- Drama; Feature films; Films for the hearing impaired; Suspense films